Saying ‘No’ In English: Refusal Strategies By Indonesian, Chinese, and Libyan EFL Learners - LESTARI KASIH (Language-Edu, 2020)
Refusal is a problematic speech acts for someone who is learning a certain language they have never used as child such as English Foreign Language (EFL) learners. Negative responses to an interlocutor’s request are often applied to approve a refusal. In the classroom interaction, learners and lecturers tend to negotiate their requests using various strategies of refusal. Miscommunication appeared when they failed to transfer pragmatic competences.   The objectives of this research is to investigate types, the response of refusal strategies, and the reason behind the use of various refusal strategies as performed by Indonesian, Chinese, and Libyan EFL learners. It involved six Indonesian EFL Learners (ILs), three Chinese EFL Learners (CLs), and three Libyan EFL Learners (LLs). They were asked to respond to six varied directions which were achieved refusal strategies. Discourse Completion Task (DCT), observation, and semi-structured interview are used to collect the data for further analysis. Findings portrayed that all three EFL Learners used regret in their refusal strategies. However, the use of refusal strategy in each context given was different. They used indirect refusal strategies as acceptances to the interlocutor.  The reason of using politeness in their refusals is to maintain interlocutor’s face and minimize Face Threatening Acts (FTA).